Design of reverse osmosis filtration system for the supply of clean water from saltwater wells in tanjung lame village. Issue 1 (February 2021) - Prayoga, Anton; Zakwan, Muhammad; Bismo, Setijo
Abstract: Groundwater sources from community wells in Tanjung Lame village, Pandeglang regency, are not suitable for consumption, due to high salinity. In addition, reverse osmosis (RO) filtration system is a typical and efficient alternative technology adopted during the processing of clean water from saltwater sources. However, large amount of pressure is usually involved for a conventional single-stage RO. The purpose of this study, therefore, was to design a multi-stage RO filtration system capable of operating at low pressures. Therefore, the adopted model with a configuration of hybrid RO/NF permeate staging has proven to produce potable water from saltwater wells in Tanjung Lame village at low pressures. Moreover, the system was operated at the first and second stage RO/NF pressure of 6 and 3 bar, respectively. Under these circumstances, salt rejection and permeate TDS were estimated at 97.02% and 86 ppm, respectively in order to obtain optimum outcome. Furthermore, the product water recovery rate was evaluated at 37%, and a permeate flow rate of 1.85 liters/minute. The systems' specific energy consumption (SEC) was estimated to be 1.802 kWh/m 3, while a reduced value of 58.39% was observed for conventional single-stage RO.